Upbuilding Representations: Biographies of historical figures in schoolbooks by Professor Lourenço Filho (Brazil/1950-70) - Cunha, Maria Teresa Santos (Historia y Memoria de la Educación, 2017)
The school texts herein investigated circulated in Brazilian elementary schools between the decades of 1950 and 1970 under a graded reading series named Série de Leitura Graduada Pedrinho. The series was comprised of four books written by Professor Manuel Bergström Lourenço Filho (1897-1970), an educator connected to principles of the Brazilian New School. These books were widely used as reading text, selling over three million copies during the studied period. This paper intends to examine the biographies of Brazilian historical figures that appeared frequently within these school texts. These biographies delivered complimentary and upbuilding representations of so-called «heroes of national history» expressed through a civic and patriotic hagiography reinforced by principles in the Republic which defended civil religiousness and secular celebrations. The presence of these heroic figures in texts constituted a symbolic community through their actions, represented as signs of Brazilianness. School texts were also analyzed as cultural artifacts of the time, which were to some extent vessels for representing and consolidating values for children as an audience